Implementasi Moderasi Beragama: Studi Penganut Tarekat Mu’tabarah di Kota Makassar - Damis, Rahmi; Nurbaethy, Andi; Ibrahim, Ibrahim; Darwin, Darwin (AL-MUTSLA, 2024)
The research question explored in this exploration is ‘How is religious moderation implemented among followers of the Mu'tabarah Tariqah (authorized sufistic schools) in Makassar City? Data collection methods employed in this exploration comprise interview and observation, in addition to documents or literature related to the subject discussed. As for the approach, this inquiry applies philosophical and phenomenological approaches. Research findings indicate that religious moderation in the view of Mu’tabarah Tariqah followers means an attitude that accepts all differences, both in terms of beliefs and culture, by prioritizing justice, tasamuh (toleration) and tawazun (balance). Implementation of religious moderation comes to forms with ground principles comprising: 1). Tolerance is a basic teaching of Islam, which respects different religious beliefs and understandings as humans are essentially the same and equally come from God. In this sense harming or despising those with different religious beliefs is equivalent to harming or despising one’s own self. 2). Social service is carried out as a form of awareness as God’s creatures who must share and love each other. It is performed in the month of Ramadan and the Ied festival (Ied al-Qurban), or even at any time when someone needs help, for humans are essentially brothers who help each other. 3) Be religious with love, that is, religious teachings are carried out based on love, since all beings are God’s creation, and they must live side by side peacefully and full of love. The implementation of religious moderation among adherents of the Mu'tabarah Tariqah results in: a) creating peace in society, b) increasing bonds of brotherhood among human beings, even among fellow creatures, who will live in harmony and peace despite their different cultures and beliefs. Other words, the bonds of friendship between fellow creatures will be well established.